Icariside II-induced mitochondrion and lysosome mediated apoptosis is counterbalanced by an autophagic salvage response in hepatoblastoma. Issue 1 (28th September 2015) - Geng, Ya-di; Zhang, Chao; Shi, Ya-min; Xia, Yuan-zheng; Guo, Chao; Yang, Lei; Kong, Ling-yi
Highlights: IS induces apoptosis through mitochondrial and lysosomal membrane permeabilization in HepG2 cells. Impairs autophagosome degradation is involved in IS-induced autophagosome accumulation in HepG2 cells. IS-induced autophagosome accumulation plays a pro-survival role through engulfing dysfunctional lysosomes and mitochondria. IS exhibits anti-tumor effect in mice transplanted with H22 liver carcinomas with the same mechanism as in vitro . Abstract: In this study, the anti-cancer effect of Icariside II (IS), a natural plant flavonoid, against hepatoblastoma cells and the underlying mechanisms were investigated. The in vitro and in vivo studies show that IS decreased the viability of human hepatoblastoma HepG2 cells in a concentration- and time-dependent manner and inhibited tumor growth in mice transplanted with H22 liver carcinomas. IS impaired mitochondria and lysosomes as evidenced by signs of induced mitochondrial and lysosomal membrane permeabilization, resulting in caspase activation and apoptosis. SQSTM1 up-regulation and autophagic flux measurements demonstrated that IS exposure also impaired autophagosome degradation which resulted in autophagosome accumulation, which plays a pro-survival role as the genetic knockdown of LC3B further sensitized the IS-treated cells. Electron microscopy images showed that autophagosome engulfs IS-impaired mitochondria and lysosomes, thus blocking cytotoxicity induced by further leakage of the hydrolases from lysosomes and pro-apoptosis members from mitochondria. In conclusion, these data suggest that IS plays multiple roles as a promising chemotherapeutic agent that induces cell apoptosis involving both mitochondrial and lysosomal damage.